PENGEMBANGAN KOMPETENSI GURU ABAD 21 MELALUI PELATIHAN PEMBELAJARAN DEEP LEARNING DI SD LABSCHOOL UNNES - Zulfikasari, Sony; Malarsih; Prihatin, Titi; Astuti, Tri; Pradipta, Anindhyta Putri (Yayasan Penelitian dan Inovasi Sumatera (YPIS), 2025)
Labschool UNNES, as a laboratory school within a teacher education institution, holds a strategic position in fostering innovative instructional practices. However, teachers’ understanding of meaningful, mindful, and joyful learning strategies within a deep learning pedagogical framework remains limited, indicating the need for targeted capacity building. This training program was designed to strengthen teachers’ competencies in implementing deep learning–oriented instruction aligned with 21st-century learning demands. The program comprised interactive training sessions, structured group discussions, and guided mentoring involving teachers from SD Labschool UNNES. Data were analyzed descriptively using a participant satisfaction survey. Findings demonstrate a marked improvement in teachers’ conceptual understanding of deep learning and their ability to design innovative instructional activities. Participants expressed highly positive evaluations of the program’s content relevance, delivery clarity, and opportunities for active engagement. Furthermore, 56.5% of participants reported the highest level of willingness to engage in subsequent collaborative initiatives. These outcomes indicate that the training not only enhanced teachers’ pedagogical literacy but also fostered motivation to apply deep learning practices in classroom settings. The program contributed to strengthening teachers’ readiness to implement meaningful, reflective, and student-centered learning experiences, while also providing a foundation for sustained development through continued mentoring and institutional collaboration.